2005
DOI: 10.1007/s00011-004-1341-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol in experimental osteoarthritis in rabbits

Abstract: A characteristic parameter in arthritis is the progressive loss of articular cartilage. This study suggests that intraarticular injections of resveratrol starting at the onset of disease may protect cartilage against the development of experimentally induced OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 31 publications
4
114
1
2
Order By: Relevance
“…Others have reported that SIRT1 associates with Runx2 and reduces its acetylation status (40). SIRT1 activation with resveratrol promotes osteoblast differentiation in vitro (40 -43) and prevents bone loss in vivo (44). These observations are the compelling systematic biological rationale for our focus on SIRT1 in bone.…”
Section: Discussionmentioning
confidence: 93%
“…Others have reported that SIRT1 associates with Runx2 and reduces its acetylation status (40). SIRT1 activation with resveratrol promotes osteoblast differentiation in vitro (40 -43) and prevents bone loss in vivo (44). These observations are the compelling systematic biological rationale for our focus on SIRT1 in bone.…”
Section: Discussionmentioning
confidence: 93%
“…Our results indicate that resveratrol exerts salutary effects on chondrocyte metabolism by reversing IL-1␤-mediated catabolic effects on proteoglycan synthesis and apoptotic cell death. Recently, Elmali et al showed that intraarticular injections of resveratrol, starting at the onset of disease, protected cartilage against the development of experimentally induced OA in rabbits (18).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, resveratrol exerts antiinflammatory or antiproliferative effects on numerous cell types, including macrophages and neutrophils (11,12), human mammary epithelial cells (13), 3T6 fibroblasts (14), and colon cancer cells (15). In vivo, resveratrol has shown beneficial effects in animal models of carcinogenesis (7), atherosclerosis (16), and Alzheimer's disease (17) and in a rabbit model of OA (18).…”
mentioning
confidence: 99%
“…To evaluate the metabolic responses of pig erythrocytes compared to human ones and in the light of the acquired experiences we also tested two different drugs: GFZ and RV which are known to bind Hb [25]- [27]. GFZ belongs to the group of fibric acid derivatives, utilized as antihyperlipidemia agents with the main aim to reduce incidence of coronary heart disease [28] [29]; RV, an important phytoalexine found in many plants, has been shown to be significantly effective in the treatment of several pathological conditions such as cancer, coronary heart disease and osteoarthritis [30]- [32]. The results shown in Figure 4 highlight a different response of the pig RBCs to the two drugs that becomes more evident when compared to human RBCs.…”
Section: Resultsmentioning
confidence: 99%